Cyprus solar water heating cluster: A missed opportunity? - Maxoulis, Christos N.; Charalampous, Harris P.; Kalogirou, Soteris A. (My University, 2007)
Cyprus is often called the “sun island” because of the amount of sunshine received all year round. The abundance of solar radiation together with a good technological base has created favourable conditions for the exploitation of solar energy on the island. This led to the development of a pioneering solar collector industry in Cyprus, which in the mid-1980s was flourishing. The result was an outstanding figure of installed solar collector area per inhabitant. Nowadays, Cyprus is cited as the country with the highest solar collector area installed per inhabitant, worldwide. This means that the local market for solar thermal collectors (for domestic applications) is now rather saturated. It was only rational to assume that Cypriot firms equipped with their gained expertise and leading edge would have safeguarded a sustainable growth and have an international orientation, focusing on exports in an emerging European and eastern Mediterranean thermal solar market. Unfortunately, this is not the case today. This paper reviews the economic performance and the competitiveness of Cyprus and the evolution of the solar water heating (SWH) industry using the cluster theory of Michael Porter. Its aim is to give insight and explanations for the success of the sector domestically, its failure with regards to exporting activity, pinpoint the industry in the European map and finally give recommendations for the cross the boarders commercial success of the industry.
Keywords: Solar water heating; Diamond model; Industry statistics